Framing Arab refugees in global news - Elsamni, Abdulrahman (AUC Knowledge Fountain, 2016)
This study examines the framing of Arab refugees and asylum seekers in the global news, represented by the news stories published on the online edition of CNN. Based on the framing theory, the quantitative content analysis found the attribution of responsibility frame to be the most salient and frequent frame in the coverage of Arab refugees and asylum seekers. The responsibility frame ascribing the Arab refugee crisis or its resolution to different actors and groups surpassed the other four news frames— human interest, conflict, economic consequences, and morality; although the five frames were existent in coverage. The lone hypothesis of the study expecting thematic frames to be more common than episodic frames was found supported. That is, the news coverage of Arab refugees tended to be thematic, as it covered the issue in the broader context, whereas episodic frames that focus on individual accounts and personal stories were less frequent. Security terms that describe Arab refugees as potential threats were found more often than the humanitarian terms that frame them as victims. The study pinpointed the lack of photos and voices of Arab refugees in the news coverage, as 90% of the relevant news articles did not include their quotes, whilst around two-thirds of the news stories did not include any of their images. The featured quotes tend to frame Arab refugees negatively, whereas the embedded photos presented more positive frames, however, the overall framing of Arab refugees and asylum seekers in CNN news stories tended to be generally balanced.